Concerned and conscious, but defenceless - the intersection of gender and generation in child malnutrition in Indonesia: a qualitative grounded theory study. Issue 1 (31st December 2020) - Vaezghasemi, Masoud; Öhman, Ann; Ng, Nawi; Hakimi, Mohammad; Eriksson, Malin
ABSTRACT: Background : Several studies in Indonesia have shown the protective effect of women-headed households on the double burden of malnutrition (coexistence of undernutrition and overnutrition in a household). Many other studies have presented a positive impact on children's health and conditions when women are educated, have higher social capital and have control of income and its intra-household allocation. However, how women's status affects the nutritional status of a household and, in particular, of children still remains understudied. Objective : In this study, our aim was to explore the role of gender relations and contextual factors for overnutrition and undernutrition among children within a household. Method : We conducted a qualitative study in two provinces of Indonesia: Central Java (urban and rural) and Jakarta (central and suburban) among 123 community members (59 men and 64 women). We utilised principles of constructivist grounded theory in conducting this study, and focus group discussions were chosen as a tool to collect data. Results : Three categories were constructed, capturing the significance of: (i) the man is dominant within the family (gendered power relations), (ii) the environment that makes the unhealthy choice the easy choice (the emerging obesogenic environment) and (iii) parents' being concerned but unable to control their children's eating habits (intersection of gender and generational relations) in child malnutrition. Conclusion : Community health and nutrition programmes should help both women and men within the context of households to acknowledge and respect women's status. More importantly, these programmes should involve men when it comes to children's nutritional habits and consider them as an important factor in the realisation of gender equality and empowerment. Furthermore, it is increasingly important to recognise the implication of the availability and accessibility of junk food among children.